Impact of multiple performance feedback and regional institutional development on enterprises’ exploratory innovation - Su, Xin; Fu, Wenxiu (Frontiers in Psychology, 2022)
With the increasing uncertainty in the external environment, exploratory innovation has gradually become the key path for enterprises to obtain core competitiveness and achieve sustainable growth. According to the behavioral theory of the firm, performance feedback is an essential driving factor affecting corporate innovation decisions. However, previous studies have ignored the consistency or inconsistency between historical and industry performance feedback, and its impact on exploratory innovation. Based on the data of Chinese companies listed from 2008 to 2019, this paper explores the impact of consistency and inconsistency between historical and industry performance feedback on enterprises’ exploratory innovation. In the cases of consistency, this study finds that the scenario of historical performance shortfall-industry performance shortfall is more likely to promote enterprises’ exploratory innovation than the industry performance surplus-historical performance surplus; in the cases of inconsistency, compared with historical performance surplus-industry performance shortfall, the scenario of historical performance shortfall-industry performance surplus is more likely to promote enterprises’ exploratory innovation. Further research shows that regional institutional development enhances these relationships. This study enriches the driving factors of enterprises’ exploratory innovation from the perspective of multiple performance feedback, which can provide decision-making references for enterprises’ exploratory innovation strategies.